Enasidenib for the treatment of relapsed or refractory acute myeloid leukemia with an isocitrate dehydrogenase 2 mutation. Issue 6 (1st November 2020) - Heiblig, Mael; Hachem-Khalife, Sabine; Willekens, Christophe; Micol, Jean-Baptiste; Paci, Angelo; Penard-Lacronique, Virginie; de Botton, Stéphane
ABSTRACT: Introduction: Isocitrate dehydrogenase 2 (IDH2) is a key metabolic enzyme that converts isocitrate to α-ketoglutarate (αKG). Somatic point mutations in IDH2 confer a gain-of-function in blast cells resulting in overproduction of D-2-hydroxyglutarate (D-2HG). High intracellular concentrations of D-2HG inhibit α-ketoglutarate-dependent dioxygenases including histone, DNA and RNA demethylases, leading to histone, DNA and RNA hypermethylation, and cell differentiation blockade. In vitro and in vivo preclinical studies have demonstrated that inhibition of IDH2-mutant enzymes with enasidenib decrease intracellular D-2HG levels, reverse epigenetic dysregulation, and release the differentiation block. The US Food and Drug Administration (FDA) approved enasidenib, a mutant-IDH2 enzyme inhibitor for patients with relapsed or refractory (R/R) IDH2 -mutated AML. Areas covered: We review the biology and prognostic significance of IDH2 mutations in AML and discuss the pharmacology, clinical efficacy, and toxicity profile of enasidenib. We highlight areas of ongoing preclinical and clinical research. Expert opinion: Enasidenib was FDA approved due to high response rates, durability of the responses that translated into an impressive OS in that heavily pretreated population. Promising ongoing clinical trials are evaluating combination therapies with enasidenib frontline.